Genetically engineered electrospinning contributes to spinal cord injury repair by regulating the immune microenvironment - Sun, Yang; Wu, Jie; Zhou, Liang; Wang, Wei; Wang, Haibo; Sun, Shaosong; Xu, Yichang; Zhang, Lichen; Jiang, Xinzhao; Zhu, Guoqing; Xi, Kun; Gu, Yong; et al. (Frontiers in Bioengineering and Biotechnology, 2024)
Spinal cord injury (SCI) is associated with microenvironment imbalance, thereby resulting in poor regeneration and recovery of the spinal cord. Gene therapy can be used to balance the inflammatory response, however target genes cannot exist in localized injured areas. Hence, a genetically engineered electrospun scaffold (GEES) to achieve long-term immunoregulation and nerve repair was constructed.By combining the microfluidic and electrospinning techniques, interleukin-10 plasmid (pIL10) was loaded into lipid nanoparticles (LNPs) (pIL10-LNP), which was encapsulated to the nerve growth factor (NGF). The results showed that the scaffold released >70% of the pIL10-LNP within 10 d and continued slow release within 30 d. In a rat T9 SCI model, the GEES significantly inhibited the inflammatory response in the acute and chronic phases of SCI by transfecting local tissues with slowrelease pIL10-LNP to promote the release of the anti-inflammatory factor IL10, thereby creating a favorable microenvironment. With the addition of NGF, the repair and regeneration of nerve tissues was effectively promoted, and the post-SCI motor function of rats improved. In conclusion, GEESs can regulate post-SCI immune responses through continuous and effective gene delivery, providing a new strategy for the construction of electrospun scaffolds for nerve repair in gene therapy.